Construction Research Congress 2016 2016
DOI: 10.1061/9780784479827.070
|View full text |Cite
|
Sign up to set email alerts
|

Integrating BIM and Project Schedule Information Using Semantic Web Technology

Abstract: A construction project requires collaboration of a large number of individuals working in different organizations to deliver the project on time and within the budget. Architecture, engineering, and construction industry spends time and money to solve the information sharing and interoperability issues between different domains. With the advent of building information modeling, a 3D CAD model of a project is used as a shared knowledge resource during the design, construction, and facility management phases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…Gudnason and Pauwels (2016) mentioned how building product information are heterogeneous, unstructured and produced in incompatible semantics in the building industry. It is a current trend that manufacturers provide their product information mostly in PDF format (Niknam et al, 2019, Costa and Madrazo, 2015, Berlo et al, 2019. Consequently, building designers are obliged to manually insert this information into their BIM tools, which is usually errorprone and inefficient (Niknam et al, 2019).…”
Section: Benefits Of the Semantic Web And Linked Data Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gudnason and Pauwels (2016) mentioned how building product information are heterogeneous, unstructured and produced in incompatible semantics in the building industry. It is a current trend that manufacturers provide their product information mostly in PDF format (Niknam et al, 2019, Costa and Madrazo, 2015, Berlo et al, 2019. Consequently, building designers are obliged to manually insert this information into their BIM tools, which is usually errorprone and inefficient (Niknam et al, 2019).…”
Section: Benefits Of the Semantic Web And Linked Data Technologiesmentioning
confidence: 99%
“…It is a current trend that manufacturers provide their product information mostly in PDF format (Niknam et al, 2019, Costa and Madrazo, 2015, Berlo et al, 2019. Consequently, building designers are obliged to manually insert this information into their BIM tools, which is usually errorprone and inefficient (Niknam et al, 2019). Hence, there is a need for an integration of product data using ontology where data is structured and connected on the web so that it can be processed by machines (Niknam and Karshenas, 2017).…”
Section: Benefits Of the Semantic Web And Linked Data Technologiesmentioning
confidence: 99%
“…The three knowledge bases include the BIM knowledge base discussed in Section 4, a cost estimating knowledge base, 32,42 and a scheduling knowledge base. 43 Information access and integration in a shared ontology architecture is demonstrated for three scenarios:…”
Section: Validationmentioning
confidence: 99%
“…SchO in Query 3 is the prefix the authors assigned to the scheduling ontology. 43 Query 3. Retrieve design and schedule properties.…”
Section: Validationmentioning
confidence: 99%
“…Each company needs to semantically define its web services and publish semantic descriptions of its web service on the web so that other companies' computer applications can communicate with it. A few studies have shown the applications of Semantic Web and Semantic Web services in AEC-FM projects [3][4][5][6][7][8][9][10]. Figure 2 shows the communication system between a BIM knowledge base [9] and a supplier's semantic web service that we have developed.…”
mentioning
confidence: 99%